MOESM1 of Differential expression of the aryl hydrocarbon receptor pathway associates with craniofacial polymorphism in sympatric Arctic charr - Ahi, Ehsan; Steinhäuser, Sophie; Pálsson, Arnar; Sigrídur Franzdóttir; Sigurdur Snorrason; Maier, Valerie; Jónsson, Zophonías (Figshare, 2015)
Additional file 1: Table S1. AhR-regulated candidate genes and available literature on their response to AhR activation, expression during craniofacial development and involvement in skeletal formation.